Tingkat pengetahuan dan sikap suami terhadap metode operasi pria di Dusun Ngasem - Ruchana Ruchana; Margono Margono; Nanik Setiyawati (Jurnal Kesehatan Ibu dan Anak, 2013)
The government imposed a national family planning programs to reduce the rater of population growth. Male participation is important in planning and reproductive health to achieve the satisfaction of sexual life. To achieve this required support for the acceptance of male participation in family planning increase knowledge and positive attitudes about the role of husband in family planning and reproductive health. This research is to know the relationship of knowledge level with husband attitude toward operation method in men at Ngasem, Selomartani, Kalasan, Sleman in 2013. The study was an observational cross-sectional design. Samples were taken by purposive sampling as many as 52 respondents. Sample is takes from a couples are in childbearing age in the Ngasem, Selomartani, Kalasan, Sleman. Bivariate data analysis use Spearman’s Rho test. Result: the majority of respondent have less toward men operating method that is as much as 27 respondents (51,9%). From the test result using Spearman Rho was found that the p-value (significant value) of 0.186 (p-value >0.05). there is no relationship between the level of knowledge of the husband’s attitude toward men in the method of operation in Ngasem, Selomartani, Kalasan, Sleman.